Contribution of Heterotrophic Diazotrophs to N2 Fixation in a Eutrophic River: Free-Living vs. Aggregate-Associated - Geisler, Eyal; Rahav, Eyal; Bar-Zeev, Edo (Frontiers in Microbiology, 2022)
Recent studies have indicated that heterotrophic diazotrophs are highly diverse and fix N2 in aquatic environments with adverse conditions for diazotrophy, such as oxic and nitrogen-rich water. In this study, we compared the activity and diversity of heterotrophic diazotrophs associated with aggregates (>12 µm) to free-living cells in the eutrophic Qishon River during the winter and summer seasons. Overall, heterotrophic N2 fixation rates were higher than expected for N-rich and well-oxygenated environments (2.6–3.5 nmol N L-1 d-1). During the summer, heterotrophic N2 fixation was mainly associated to aggregates (74%±24%), whereas during the winter the bulk diazotrophic activity was mostly ascribed to the free-living fraction (90%±6%). In addition, immunolabeled micrographs indicated the presence of aggregate-associated heterotrophic diazotrophs in both of seasons, while phototrophic diazotrophs were also captured during the winter. The richness of free-living and aggregate-associated heterotrophic diazotrophs were overall similar, yet the evenness of the later was significantly smaller, indicating on few species that were likely particle specialists. The differences in the activity, micro-localization and diversity of the diazotrophic community were mostly attributed to spatiotemporal changes in the ambient C:N ratios and the total organic carbon concentrations. Taken together, our results shed new light on the contribution of heterotrophic diazotrophs to N2 fixation in eutrophic environments that may theoretically impair diazotrophy.